X-ray irradiated LDPE/PP blends with high mechanical and dielectric performance - Alkan, Ümit; Kılıç, Mehmet; Karabul, Yaşar; Çağlar, Mustafa; İçelli, Orhan; Güven Özdemir, Zeynep (Wiley, 2018)
In this study, the influences of polypropylene (PP) additive (varying from 20% to 80% wt) and low dose X-ray irradiation (changing from 25 to 100 Gy) on the mechanical and dielectric properties of low-density polyethylene (LDPE) were investigated. LDPE/PP film blends were prepared by hot press technique. While the highest Young modulus and tensile strength were observed for the 20%LDPE/80%PP blend at 25 Gy X-ray irradiation, the same blend had the highest energy at break and percentage strain at break values for 50 Gy X-ray exposure. These results also indicated a chain scission in the material. The differential scanning calorimetry curves also indicated a chain scission and crosslinking effects in the blends due to X-ray irradiation. Hence, the higher concentration of PP additive and exposure of low dose X-ray resulted in a polymer composite with high mechanical performance. On the other hand, the dielectric investigations revealed that the 25 Gy X-ray irradiated 20%LDPE/80%PP blend may also attract attention for capacitor applications due to its increased static dielectric constant and reduced dielectric loss.
WOS: 000432005700019
Keywords: Blends; Dielectric Properties; Irradiation; Mechanical Properties; Thermoplastics